The computational age-at-death estimation from 3D surface models of the adult pubic symphysis using data mining methods - Kotěrová, Anežka; Štepanovský, Michal; Buk, Zdeněk; Brůžek, Jaroslav; Techataweewan, Nawaporn; Velemínská, Jana (Scientific reports, 2022)
Age-at-death estimation of adult skeletal remains is a key part of biological profile estimation, yet it remains problematic for several reasons. One of them may be the subjective nature of the evaluation of age-related changes, or the fact that the human eye is unable to detect all the relevant surface changes. We have several aims: (1) to validate already existing computer models for age estimation; (2) to propose our own expert system based on computational approaches to eliminate the factor of subjectivity and to use the full potential of surface changes on an articulation area; and (3) to determine what age range the pubic symphysis is useful for age estimation. A sample of 483 3D representations of the pubic symphyseal surfaces from the ossa coxae of adult individuals coming from four European (two from Portugal, one from Switzerland and Greece) and one Asian (Thailand) identified skeletal collections was used. A validation of published algorithms showed very high error in our dataset-the Mean Absolute Error (MAE) ranged from 16.2 and 25.1 years. Two completely new approaches were proposed in this paper: SASS (Simple Automated Symphyseal Surface-based) and AANNESS (Advanced Automated Neural Network-grounded Extended Symphyseal Surface-based), whose MAE values are 11.7 and 10.6 years, respectively. Lastly, it was demonstrated that our models could estimate the age-at-death using the pubic symphysis over the entire adult age range. The proposed models offer objective age estimates with low estimation error (compared to traditional visual methods) and are able to estimate age using the pubic symphysis across the entire adult age range.
Keywords: Forensic Anthropology; Imaging, Three-Dimensional; soudní antropologie; zobrazování trojrozměrné; dospělí; Adult; Data Mining; určení kostního věku; Humans; lidé; symphysis pubica; Pubic Symphysis; data mining; Age Determination by Skeleton